Penyuluhan Peningkatan Kualitas Bunga Mawar dengan Pupuk NPK Mutiara dan Polybag di Kelompok PKK Pakuan Baru Kota Jambi - Hasriati Nasution; Asmadi Saad; Yusfaneti (Studium: Jurnal Pengabdian Kepada Masyarakat, 2023)
Roses (Rosa hybrida) are known as the “Prince of Flowers” due to their beauty and fragrance. This article discusses the improvement of rose quality through the use of NPK Mutiara fertilizer in the PKK group in Pakuan Baru, Jambi City. The community program aims to enhance the skills of women in the PKK group in cultivating roses, enabling them to achieve robust growth and abundant blooming with vibrant colors. The team provided rose seedlings, polybags, NPK Mutiara fertilizer, potting soil, and water. The results of this program showed enthusiasm and understanding among the PKK women regarding the use of this fertilizer for roses.